YIELD BY PRODUCT THROUGH THE ACTIVITY BASED COSTING . A CASE IN THE INDUSTRIAL SECTOR - Vergiú Canto, Jorge (2005)
One of the main problems for all companies, especially when more than a product is made, is the assignment of indirect costs to the product, taking into account that using the traditional system of costs of finished products get distortions. On the other hand, in the Activity Based Costing (ABC) these costs are assigned to products, taking into account the performance of activities, used resources and cost object.